2018
DOI: 10.1088/1361-6528/aaabe8
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-assisted post-growth substitution of tellurium into molybdenum disulfide monolayers with tunable compositions

Abstract: Herein we report the successful doping of tellurium (Te) into molybdenum disulfide (MoS) monolayers to form MoS Te alloy with variable compositions via a hydrogen-assisted post-growth chemical vapor deposition process. It is confirmed that H plays an indispensable role in the Te substitution into as-grown MoS monolayers. Atomic-resolution transmission electron microscopy allows us to determine the lattice sites and the concentration of introduced Te atoms. At a relatively low concentration, tellurium is only s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Again, lighter impurities lead to additional peaks at higher frequencies and heavier impurities at lower frequencies, but the features that are most likely to be observed in experiments are those falling above the A 2 mode or inside the gap between E mode and the LA(M) edge. In fact, such features have been reported in the literature for MoS 2 with light Se alloying at about 270 cm −1 [9,10,31,68] and with light Te alloying at about 243 cm −1 [69], agreeing well with our calculations.…”
Section: Impurities In H-mos2supporting
confidence: 93%
“…Again, lighter impurities lead to additional peaks at higher frequencies and heavier impurities at lower frequencies, but the features that are most likely to be observed in experiments are those falling above the A 2 mode or inside the gap between E mode and the LA(M) edge. In fact, such features have been reported in the literature for MoS 2 with light Se alloying at about 270 cm −1 [9,10,31,68] and with light Te alloying at about 243 cm −1 [69], agreeing well with our calculations.…”
Section: Impurities In H-mos2supporting
confidence: 93%
“…Regarding the possible synthesis of the most stable blend structure, we can get inspiration from the reported synthesis work of random MoS 2Àx Te x alloys in previous studies. [76][77][78][79][80][81] For example, Yun et al synthesized monolayer MoS 2 on SiO 2 /Si wafers by chemical vapor deposition (CVD) at first, and then transferred MoS 2 to a NaOH-coated substrate on a ceramic crucible. Finally, two-zone CVD was introduced to achieve the tellurization process.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, chemical vapor deposition (CVD) synthesis provides much better control on the crystal thickness and is more promising for large‐scale production. Recently, it was reported that tellurium alloys can be synthesized using CVD as well, including hydrogen‐assisted post‐growth substitution of tellurium into MoS 2 , [ 29 ] growing MoSe 2(1− x ) Te 2 x alloys using sodium cholate, [ 30 ] tellurizing MoS 2 and WS 2 via alkali metal scooter, [ 28 ] and synthesizing WTe 2 S 2(1− x ) using sodium chloride. [ 31 ] However, the ternary telluride heterostructures and their electronic and photonic devices remain unexplored.…”
Section: Figurementioning
confidence: 99%